EXPERIENCE OF TEACHER COMMUNICATION IN TEACHING CHILDREN WITH DOWN SINDROM (Phenomenological Study on Down Syndrome Children in SLB YPPLB Padang) - Febrianty Hanif, Whulan; Chatra, Emeraldy; Arif, Ernita (Universitas Telkom, 2024)
Teachers are a central figure in the world of education especially when there is a developing teaching interaction process and are the most responsible for developing learners' potential. A teacher's role in the learning process is crucial to the shaping of a child's character. Teachers directly play a role in influencing what they learn, how they receive learning, and what they look like in interacting in their social lives. The problem in this research is how the teacher's communication experience in teaching a child down syndrome in the SLB YPPLB padang. The research method used is qualitative research. The paradigm used in this study is a constructive paradigm with the phenomenon approaching Edmund husserl. Research shows that the process of communication built into teacher and child down syndrome is pure interpersonal communication. Communication is done in person so that teachers and down syndrome can detect immediate reactions and can provide immediate feedback. The communication process consists of the seven stages, that is; The rendering stage, the encoding stage, the delivery stage, the travel stage, the reception stage, the reverse encoding stage, and the interpretive stage. Then, success in communication came to include five things: Information transparency, empathy, a supportive attitude, a positive attitude, and space. There is a breakdown in communication, that is; Misunderstandings, language differences, and special needs. Nonverbal communication in the study contained attributes, tone of speech, touch, sitting position, and the use of time. The transcendental meaning of the teacher's experience is that of embracing and feeling fulfillment. Keywords: communication experience, teachers, down syndrome, interpersonal communication